COMPARISON OF PHYSICAL FITNESS IN STUDENTS OF ANÁPOLIS-GO ABOUT PLANTAR ARCH FORMATION (Fiep Bulletin - online, 2013)
Due to the condition of the plantar arch being a limiting factor for physical fitness in adolescent people, it was established as objective of this work to register, in adolescent people practicing various sports, the incidence of flat, cavus and neutral foot, comparing the components of physical fitness of young people according to the foot type. The study was conducted with a sample of 331 boys and 226 girls. The variables measured were body fat percentage (% BF) (triceps + calf), aerobic endurance test (1600m), agility (square test), displacement speed (shot 20m), flexibility (modified form of the sit and reach test) and explosive power (horizontal jump test). All measurements and classifications were according to the protocol (PROESP BR-2007). The foot type evaluation was done by the plantigram test. Comparison between the three groups, concerning the variables of physical performance, was through a one-way ANOVA. It was identified 26 volunteers with flat feet and two cavus feet that were considered pathological. These volunteers were excluded from the study. The remaining 529 youngs had 14.2  3.1 years, %BF = 16.69  3.47 to boys and 25.32  3.17 for girls. Overall 86 (16.2%) had cavus foot, 219 (41.4%) were detected with neutral pronation and the remaining 224 (43.4%) young people have flat feet. Individuals with pes cavus were significantly worse than the others as to agility. In the measurement of displacement speed with people with neutral pronation showed the worst performance. The less time spent to reach the 1609m and VO2max. were individuals with flat feet. They also showed a better explosive power of the lower limbs, identified by the horizontal jump test. As for flexibility there was no significant difference between groups. It was concluded that there is a predominance of flat feet among the evaluated, and these had a better aerobic capacity and strength of lower limbs. The variable speed, with individuals with underpronation and neutral pronation showed up statistically equal. The neutral pronation represented the worst performance in speed.
Keywords: pes planus; pes cavus; physical fitness; plantar arch; physical performance.